Cocoa Cultivation Development to Improve the Economy of Farmers in Sidrap, South Sulawesi - Parawansa, Ayu Kartini; Kalla, Rastina; Aslam, Annisa Paramaswary (Southeast Asia Journal of Business, Accounting, and Entrepreneurship, 2025)
The aim of this study is to evaluate the impact of training and development programs on improving cocoa cultivation practices among farmers in Sidrap District, South Sulawesi, and to assess their knowledge and skills in disease control, productivity technology, and market strategies. This is a community-based intervention study using a mixed-methods approach, combining both qualitative and quantitative assessments to measure the impact of the training program. The study was conducted in the Betao Riawa Mampise farmer group in Sidrap District, South Sulawesi, from August 2024 to November 2024. The study involved 22 cocoa farmers from the Betao Riawa Mampise group. The participants were provided with extension sessions covering cocoa disease management, eco-friendly farming practices, and the use of technology for increased productivity. In addition, a digital marketing workshop was held to train farmers on utilizing platforms like Facebook and Tokopedia to sell cocoa products. Pre- and post-training assessments were conducted to measure improvements in knowledge and skills. A survey was also administered to evaluate the overall impact of the program. The training program effectively improved the farmers' knowledge of cocoa disease management, eco-friendly farming practices, and digital marketing strategies. This non-invasive approach could significantly enhance cocoa production and marketing, offering a sustainable way to increase income for cocoa farmers in Sidrap District. However, further support in technology access is necessary to ensure that all farmers benefit equally.